DAMPAK KEKUASAAN MARITIM SRIWIJAYA TERHADAP MASUKNYA PEDAGANG MUSLIM DI PALEMBANG ABAD VII-IX MASEHI - Ahmad Berkah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
Research in title “The impact of Sriwijaya Maritime Power toward the Entrance of Muslim Trade in Palembang in VII-IX Century” is based on the power of Sriwijaya maritime that dominated all of the International trade voyage path which was sailed by the foreign merchant including Arabic Muslim traders. The Arabic Muslim traders which sailed and traded to China must go across trade voyage paths of Sriwijaya, thus, the merchants stopped over in the Kingdom center of Sriwijaya located in Palembang. The objective of the study is to analyze the history of development of Sriwijaya’s maritime power, analyzing the sailing and trading path and the relationship of Sriwijaya and the foreign country, and the impact of Sriwijaya’s maritime power toward the entrance of Muslimtraders in Palembang in VII-IX century. This study is in the form of Qualitative research design which is library research., by analyzing thoroughly every single relevant literature. The approach of the research is by using historical method approach which are, heuristic, verification, interpretation, and historiograsion, and politicoligist and economologist scholarship. Moreover, the source of the data were primer and seconder data. Data collection technique as heuristic and verification. To analyze the data, it was used interpretation, then it was conducted the last step that was historyografy or a writing of history. This research concludes that the history of development of Sriwijaya appearing as the ruler of the largest maritime power in Nusantara was supported by their great army and a management of a strong and respected leader.Sriwijaya easily controlled strategic shipping paths, such as the Strait of Malacca, Bangka Strait, Sunda Strait, Karimata Strait, and all shipping lanes in the Nusantara.The condition of the shipping Routes initially frightened Muslim traders, because of the large number of pirates, having successfully controlled by Sriwijaya's maritime power, it became safe and comfortable to go through. And it was required to stop at the harbor or in the center of Sriwijaya Kingdom located in Palembang. In addition, Sriwijaya's relationships with foreign countries, namely Arab, India, China were carried out by Sriwijaya for the recognition of sovereignty and Sriwijaya's power strengthening in the trade shipping paths. Sriwijaya with its maritime power and cooperating with the Sea People to secure the cruise line to the center of Sriwijaya from pirates as well as increasing the confidence of Muslim traders both in trade and security guarantees on the way back from the center of Sriwijaya and access for Muslim traders in the process of Islamization through trade routes in the territory of Sriwijaya kingdom.